Foundations of Christian Bioethics: Metaphysical, Conceptual, and Biblical - Cherry, Mark J. (Christian bioethics, 2023)
How can we definitively determine which biomedical choices are morally correct and which engage in seriously wrongful acts? Depending on whom one asks, one is informed that choices such as abortion, euthanasia, and significant body modification involve real moral harm (either as forms of murder or as denying the goodness of the body that God has provided), or that disallowing such "medical care" violates the basic rights of persons (where abortion, active euthanasia, and body modification are appreciated as positive expressions of personal autonomy). Secular bioethics appears no longer able to appreciate what could possibly be wrong with such activities, provided that the individuals involved consent in some fashion. Indeed, many actions that were once openly and easily recognized as sinful have become so commonplace, as well as politically desirable, as to appear as if they were obviously good. As the authors in this issue of Christian Bioethics explore, fully to appreciate the serious moral issues raised by modern medicine requires a foundational orientation to the Christian God.